Inzech! Inbotch! : yeItiyopiya guzo - Mesfin Wolde-Mariam. (Addis Ababa.: : [publisher not identified], 2010)
On the political history of Ethiopia.
Includes bibliographical references (pages 254-257) and index.
Includes bibliographical references (pages 254-257) and index.
In Amharic.
Keywords: Human Rights Law; Human Rights